The photography as a tool of social communication: the role of visual narrative in shaping public discourses - Brus, Mariana (Global Prosperity, 2025)
Abstract. The article examines photography as a tool of social communication, functioning as an active agent in shaping public discourses through visual narratives. It is emphasized that in the contemporary digital environment, where mobile devices and social networks enable the instant dissemination of images to millions of people, photography ceases to be merely an illustration of events and becomes a proactive means of influencing cognition, emotions, memory, political behavior, and social mobilization. The photography does a lot of things, actually. For one, it really boosts how believable messages seem to be – our brains just eat up visual stuff faster than words, and we tend to treat what we see as solid proof of something happening. Second, photographs generate emotions such as empathy and solidarity, which makes us more sensitive to social issues. Third, the identity function of photography helps to create collective memory and narratives of national identity. Finally, the media-structural function involves the interaction between the author, the distribution platform and the audience, which affects how information is perceived and interpreted. It is also important to consider the role of humanistic and documentary photography in the context of social events, such as funerals of fallen soldiers. Ethical, moral and legal issues arise here, as it is important to respect the rights of the participants and their families, as well as to find a balance between the right of society to information and the dignity of those who have died. Photography in the media space performs the function of documentation and scientific research, and at the same time is a tool that shapes social narratives, attracts attention, influences public opinion, and supports international solidarity. The effectiveness of photography as a social tool depends on several factors, including the professional skills of the authors, the ethical approach to the content, the use of retouching and consideration of the psychological impact on the audience. Also important are the context in which the photograph is distributed and the platform used. In general, we can say that photography combines documentary and semiotic potential. It is able to transform the collective narrative, shape public discourses and plays an important role in preserving cultural, historical and national memory. In addition, in the digital age, photography is becoming an essential tool for social interaction.